PENGARUH JENIS KONSORSIUM BAKTERI PUPUK HAYATI TERHADAP EFISIENSI PUPUK ANORGANIK DAN PRODUKTIVITAS TANAMAN TOMAT (Solanum lycopersicum L.) - Nurma Yanti Ningtyas, Dewi; Mustikasari Dewi, Sheli; Rijal Giffari, Fahri; Septianugraha, Reza; Anwar, Hasan (Jurnal Biogenerasi, 2025)
The aim of this research is to analyze the effect of different types of organic fertilizer (solid biological, liquid biological and foliar) on the growth and productivity of tomato plants. This research was carried out for 3 months starting from February to April 2024. This research used a Randomized Block Design (RAK) consisting of 14 treatments, namely: solid biological fertilizer (100%), liquid biological fertilizer (100%) and foliar organic fertilizer (100%) with inorganic fertilizer doses of 25%, 50% and 75%. There were 14 treatment combinations with 3 repetitions. The observation variables are plant height, number of leaves, stem diameter and plant weight. The results of the research showed that the best treatment for plant height was liquid biofertilizer + 25% dose of inorganic fertilizer (83.47 cm), for number of leaves, namely liquid biofertilizer and leaf organic fertilizer (7 pieces), for stem diameter, 100% biofertilizer (6.20 cm) and for plant weight, namely organic leaf fertilizer + 75% dose of inorganic fertilizer (56.39 g).